2004
DOI: 10.1103/physrevb.70.235409
|View full text |Cite
|
Sign up to set email alerts
|

Structure and morphology of the tenfold surface of decagonalAl71.8Ni14.8Co13.4in its low-temperature random tiling type-I modification

Abstract: We have investigated the structure and morphology of the tenfold surface of decagonal Al 71.8 Ni 14.8 Co 13.4 by highly surface sensitive He atom scattering (HAS), high resolution low energy electron diffraction (SPA-LEED), and low temperature scanning tunneling microscopy (STM). The SPA-LEED patterns reveal more than 500 individual diffraction spots in the k-vector range of ͉k ʈ ͉ Ͻ 3 Å −1 . The positions of all observed diffraction spots agree with the surface projections of the reciprocal lattice structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…STM shows wide terraces separated by steps of 2Å height [35,37,39,40]. High resolution images show pentagonal features, which have the same orientation in a single terrace, but are rotated by 36…”
Section: The Tenfold Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…STM shows wide terraces separated by steps of 2Å height [35,37,39,40]. High resolution images show pentagonal features, which have the same orientation in a single terrace, but are rotated by 36…”
Section: The Tenfold Surfacementioning
confidence: 99%
“…Helium atom scattering (HAS) shows a specular (reflected peak) intensity comparable to that of high-quality cleaved surfaces of periodic crystals, e.g., GaAs(110) [45]. LEED patterns from the surface show a dense pattern of spots distributed with symmetry expected from the bulk [35]. An example of a spot-profile-analysis-LEED image from the tenfold surface of the type-I superstructure is given in figure 3.…”
Section: The Tenfold Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The 10-fold surface of the Al-Ni-Co decagonal quasicrystal-the surface that is quasicrystalline in both dimensions-has been studied by low-energy electron diffraction ͑LEED͒, ion scattering spectroscopy, and scanning tunneling microscopy 6-10 ͑STM͒, but there are still important issues, such as atomic structure and composition, that remain controversial. 8,9 Some authors have attributed sites of high tunneling probability in the STM images to transition metal atoms, 8 while others have identified these sites as Al atoms. 7,9 A further point of discussion is whether the surface termination is enriched in Al relative to the bulk composition.…”
mentioning
confidence: 99%
“…8,9 Some authors have attributed sites of high tunneling probability in the STM images to transition metal atoms, 8 while others have identified these sites as Al atoms. 7,9 A further point of discussion is whether the surface termination is enriched in Al relative to the bulk composition. 6,7 In contrast to the 10-fold surface however, only a few studies of the 2-fold surface 6,11,12 have been reported.…”
mentioning
confidence: 99%